Orientalism: Western conception of the orient - Said, Edward W. (Penguin, 1995)
The author surveys the history and nature of Western attitudes towards the East, considering Orientalism as a powerful European ideological creation. He traces his view through the writings of Homer, Nerval and Flaubert, Disraeli and Kipling, whose imaginative depictions have greatly contributed to the West's romantic and exotic picture of the Orient. Drawing on his own experience as an Arab Palestinian living in the West, the author examines how these ideas can be a reflection of European imperialism and racism. -- from http://trove.nla.gov.au (Sep. 22, 2011).